Development and characterization of 3D-printed feed spacers for spiral wound membrane systems. (15th March 2016) - Siddiqui, Amber; Farhat, Nadia; Bucs, Szilárd S.; Linares, Rodrigo Valladares; Picioreanu, Cristian; Kruithof, Joop C.; van Loosdrecht, Mark C.M.; Kidwell, James; Vrouwenvelder, Johannes S.
Abstract: Feed spacers are important for the impact of biofouling on the performance of spiral-wound reverse osmosis (RO) and nanofiltration (NF) membrane systems. The objective of this study was to propose a strategy for developing, characterizing, and testing of feed spacers by numerical modeling, three-dimensional (3D) printing of feed spacers and experimental membrane fouling simulator (MFS) studies. The results of numerical modeling on the hydrodynamic behavior of various feed spacer geometries suggested that the impact of spacers on hydrodynamics and biofouling can be improved. A good agreement was found for the modeled and measured relationship between linear flow velocity and pressure drop for feed spacers with the same geometry, indicating that modeling can serve as the first step in spacer characterization. An experimental comparison study of a feed spacer currently applied in practice and a 3D printed feed spacer with the same geometry showed (i) similar hydrodynamic behavior, (ii) similar pressure drop development with time and (iii) similar biomass accumulation during MFS biofouling studies, indicating that 3D printing technology is an alternative strategy for development of thin feed spacers with a complex geometry. Based on the numerical modeling results, a modified feed spacer with low pressure drop was selected for 3D printing. The comparison study of the feed spacer from practice and the modified geometry 3D printed feed spacer established that the 3D printed spacer had (i) a lower pressure drop during hydrodynamic testing, (ii) a lower pressure drop increase in time with the same accumulated biomass amount, indicating that modifying feed spacer geometries can reduce the impact of accumulated biomass on membrane performance. The combination of numerical modeling of feed spacers and experimental testing of 3D printed feed spacers is a promising strategy (rapid, low cost and representative) to develop advanced feed spacers aiming to reduce the impact of biofilm formation on membrane performance and to improve the cleanability of spiral-wound NF and RO membrane systems. The proposed strategy may also be suitable to develop spacers in e.g. forward osmosis (FO), reverse electrodialysis (RED), membrane distillation (MD), and electrodeionisation (EDI) membrane systems. Highlights: Comparison of practical and 3D printed spacers with the same and modified geometry. Numerical modeling and experimental studies on hydraulics and biofouling. Similar hydraulics and biofouling development for same geometry feed spacers. Improved hydraulics and low biofouling impact by feed spacer with modified geometry. Proposal for a strategy to develop and test a new generation feed spacer.